ANALISIS CAMPUR KODE PADA WACANA BAHASA BALI - Ida Bagus - Rai; I Wayan Gede - Wisnu; Ida Ayu Putu Purnami; Sang Ayu Putu Sriasih (Universitas Pendidikan Ganesha, 2016)
This study is a qualitative research aimed at the Balinese language discourse. This research was done on the grounds separately to determine the use of the Balinese language used in Balinese language discourse. It is also to see how big a role other languages spoken in the discourse of the Balinese language, resulting in the phenomenon of code-mixing. Subjects in this study is the discourse of the Balinese language. The object of this research are the Code Mixing of Balinese language discourse. Data collection methods used were observation and documentation. While this research instrument was the data card. Data were analyzed through the stages; data reduction, identification, classification, presentation, and drawing conclusions. The results of this study can be seen that there was code-mixing in Yong Sagita songs on the album. Languages are often appears on code-mixing into is Indonesian. Code-mixing types were based on speech level language, the level of the word is the type most commonly found in the study, because the level of the most easily understood words. Factors that cause the interference of code in a pop song Bali Yong Sagita is because of the speakers and linguistic factors. Keywords: Mixed code, Discourse, Language Bali. ABSTRAK Penelitian ini adalah penelitian kualitatif yang ditujukan pada Wacana Bahasa Bali. Penelitian ini dilakukan dengan alasan utnuk mengetahui penggunaan bahasa Bali yang digunakan pada Wacana Bahasa Bali. Selain itu juga melihat seberapa besar peranan bahasa lain yang digunakan pada Wacana Bahasa Bali, sehingga terjadi fenomena campur kode. Subjek dalam penelitian ini adalah Wacana Bahasa Bali. Objek dalam penelitian ini adalah Campur Kode yang terdapat pada wacana Bahasa Bali. Metode pengumpulan data yang digunakan adalah observasi dan dokumentasi. Sedangkan Instrumen penelitian ini menggunakan kartu data. Data dianalisis melalui tahapan; reduksi data, identifikasi, klasifikasi, penyajian, dan penarikan simpulan. Hasil dari penelitian ini dapat diketahui bahwa terjadi campur kode pada album lagu Yong Sagita. Bahasa yang sering muncul pada campur kode ke dalam adalah bahasa Indonesia. Jenis campur kode berdasarkan tingkat tutur bahasa, tataran kata merupakan jenis yang paling banyak ditemukan pada penelitian, karena tataran kata paling mudah dipahami. Faktor yang menyebabkan adanya campur kode dalam lagu pop Bali Yong Sagita adalah karena faktor pembicara dan faktor kebahasaan. Kata kunci: Campur kode, Wacana, Bahasa Bali.